2015
DOI: 10.1016/j.imbio.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal C4b-binding protein is processed and degraded during transit through the duct and is not essential for fertility

Abstract: C4b-binding protein (C4BP) is known as one of the circulating complement regulators that prevents excessive activation of the host-defense complement system. We have reported previously that C4BP is expressed abundantly in the rodent epididymis, one of the male reproductive organs connecting the testis and vas deferens, where immature spermatozoa acquire their motility and fertilizing ability during their transit through the duct. Epididymal C4BP (EpC4BP) is synthesized androgen-dependently by the epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Complement complexes are involved and seem to be important in healthy pregnancies, while the role is yet unclear [79]. Unexpectedly, transgenic mice lacking C4BP appear to have an overall normal phenotype [80]. However, we observed that homozygous C4BP knockout mice often die during second or third pregnancy (unpublished observation).…”
Section: Implications In Recurrent Pregnancy Lossmentioning
confidence: 73%
“…Complement complexes are involved and seem to be important in healthy pregnancies, while the role is yet unclear [79]. Unexpectedly, transgenic mice lacking C4BP appear to have an overall normal phenotype [80]. However, we observed that homozygous C4BP knockout mice often die during second or third pregnancy (unpublished observation).…”
Section: Implications In Recurrent Pregnancy Lossmentioning
confidence: 73%
“…C57BL/6 C4BP-deficient mice were provided by MI Nonaka [15]. HEK293 cells stably expressing mouse TLR4, mouse MD-2, and mouse CD14 (HEK293-TLR4/MD-2/CD14), and those stably expressing mouse TLR3 (HEK293-TLR3) were purchased from Invi-voGen.…”
Section: Cells and Micementioning
confidence: 99%
“…These RAW264.7 cells were cultured in complete DMEM supplemented with 1 lgÁmL À1 puromycin. C57BL/6 C4BP-deficient mice were provided by MI Nonaka [15].…”
Section: Cells and Micementioning
confidence: 99%
“…C57BL/6 C4BP-deficient mice were provided by Dr MI Nonaka. 18 Detection and microsequencing of 25-kDa molecule Cell surface biotinylation of A20 cells were performed as described previously. 19 Briefly, cells ($5 Â 10 7 cells/ ml) were suspended in saline containing 100 mM HEPES (pH 8.0), and then biotinylated with sulfosuccinimidobiotin (Pierce, Rockford, IL, USA) at a final concentration of 0.5 mg/ml.…”
Section: Cells and Micementioning
confidence: 99%